Tuta absoluta's population genetic structure across Africa: Two well-delineated but weakly differentiated groups suggesting few introductions and significant gene flow - (:unkn) unknown (My University, 2025)
All DNA extracts and genotypes are preserved at the 'Centre de Biologie pour la Gestion des Populations' (CBGP), Montferrier sur Lez (France), under the authority of N. Gauthier. The data and related documentations that support the findings of this study are openly available in DataSuds repository (IRD, France) at 10.23708/RE36VC. Data reuse is granted under CC-BY-SA licence.
Keywords: African Research